Naposo Nauli Bulung: Existence, Role and Continuity of Islamic Education Institutions Based on Local Wisdom in Instilling Islamic Education Values in the Community - Siregar, Agus Prianto; Mahariah, Mahariah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
This research aims to present the tradition of Naposo Nauli Bulung who are young people who are the hope for the nation and religion, they will be the connecting rope for the future development of our nation and country. This is motivated by the lack of interest in today's easy generation, therefore with the provision of strong knowledge, and mental strength, Naposo Nauli Bulung (youth) in our country will be a very big hope for the future of our country Indonesia. This research uses a qualitative method with a case study approach. The results showed that, the Naposo Nauli Bulung tradition of parents really want their children to be good and virtuous children who are far from the influence of bad environments such as drugs, brawls, sinning, gambling and other forms of crime. Especially in the era of the advancement of technology in the form of cellphones and other electronics, it is a catastrophe that has a very big influence on damaging the morals and character of today's young people. Therefore, Naposo Nauli Bulung plays a very important role in maintaining the values of national and religious education so that they become young people who are useful and useful to the community environment, especially to their families.